STUDENTS’ PROBLEM IN WRITING DESCRIPTIVE TEXT AT THE SEVENTH GRADE OF SMP SWASTA KRISTEN BNKP TELUK DALAM - Duha, Lesti (Universitas Nias Raya, 2024)
This research aimed at finding out the students’ problem in writing descriptive text at the seventh grade. This research was designed by using qualitative research with descriptive approach. The data of this research were obtained from the students’ worksheets about writing descriptive text and interview result. The data obtained were analyzing by using Miles and Huberman (1984) theory, there are: data reduction, data display, and conclusion drawing/verification. The result of this research showed that most students have problem in developing their idea to create content, low mastery of text organization, students did not know the grammar correctly, and students still did not understand the mechanic in writing paragraph especially in the spelling, capitalization and punctuation, and have difficulties in vocabulary. The factors which caused students problem in writing descriptive text were lack of knowledge, lack of grammar understanding and lack of vocabulary. It is suggested to the English teacher to teach students intensively about how to use organization, content, grammar, mechanic and vocabulary in writing descriptive text. For the learners the researcher suggested to be more in diligent studying and practice producing descriptive texts as a means to enhance their writing skills.